Problem-based learning and its contribution to the analytical skills of 5th grade students in science learning - Noviana, Nadia Dian; Maryani, Ika (Universitas Ahmad Dahlan, 2024)
Analytical skills are essential for students to understand scientific concepts and solve problems effectively. However, conventional learning methods often fail to optimally develop these skills in elementary school students. This research aims to analyze the effect of the problem-based learning (PBL) model on the analytical skills of fifth-grade students in science learning. The method used is a quasi-experimental design with a matching pretest-posttest control group design. The sample of this study consists of two classes, namely the experimental class that applies the PBL model and the control class that uses conventional learning methods. Data collection was conducted through descriptive tests to assess students' analytical skills and observation sheets to determine the implementation of PBL. The results of the study indicate that there is a significant difference in improving analytical skills between students who learn using the PBL model compared to those who use conventional methods. Therefore, the PBL model can be an alternative to enhance students' analytical skills in science learning. These findings implied that integrating PBL into the curriculum can support the development of higher-order thinking skills in elementary education.